PERAN KEBIJAKAN DAN PROGRAM DINAS PEMUDA DAN OLAHRAGA PROVINSI JAWA TIMUR DALAM PENINGKATAN INDEKS PEMBANGUNAN PEMUDA (IPP) - Ramadhan Agung Suriansya; Shabrina Aulia Adam (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Youth development is a strategic aspect of enhancing human resource quality and regional competitiveness, which in Indonesia is measured through the Youth Development Index (YDI) covering five domains: education, health and well-being, employment opportunities, participation and leadership, and gender and discrimination. East Java Province has a large youth population and a YDI score comparable to the national average; however, several indicators remain stagnant or vulnerable, particularly in the domains of health and well-being and employment. This condition raises questions about the extent to which youth policies and programs implemented by the East Java Provincial Youth and Sports Office (Dispora Jatim) contribute to improving the YDI. This study aims to analyze the role of Dispora Jatim’s policies and programs in enhancing the YDI and to identify gaps between program design and YDI indicators. Using a descriptive-analytical approach, this research applies public policy analysis and secondary data analysis based on the 2023 YDI report, the 2025–2026 Strategic Plan of Dispora Jatim, and supporting statistical data. The findings indicate that while Dispora Jatim’s programs are normatively aligned with YDI dimensions, their impact on several indicators remains limited due to a stronger emphasis on program outputs rather than sustainable social outcomes, highlighting the need for YDI-based policy evaluation and stronger cross-sectoral integration in youth development.